1994
DOI: 10.1002/ptr.2650080507
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective studies of a fraction from the fruits of Terminalia belerica roxb. On experimental liver injury in rodents

Abstract: The effects of an orally administered fraction (TB5) from the fruits of Tenninalia belerica in experimental liver injury induced by carbon tetrachloride (CC4) were studied. Hexobarbitone-induced sleep, zoxazolamineinduced paralysis, transaminases, bilirubin, total protein in serum and microsomal lipid peroxidation and triglycerides in liver were used as indices of liver injury.A significant hepatoprotective effect was observed as evident from shortened hexobarbitone 'sleep time' and zoxazolamine 'paralysis tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…CCl 4 treatment also causes significant increase in bilirubin level (Hyperbilirubinemia), because CCI 4 is also one of the most useful model to the severity of necrosis (Zimmerman, 1973). While there was no change in total protein level, these findings were in accordance with the observation that protein in general and albumin level in particular remains unchanged in acute liver damage (Anand et al, 1994). This brief period might not be sufficient to demonstrate any rise in serum protein levels.…”
Section: Discussionsupporting
confidence: 87%
“…CCl 4 treatment also causes significant increase in bilirubin level (Hyperbilirubinemia), because CCI 4 is also one of the most useful model to the severity of necrosis (Zimmerman, 1973). While there was no change in total protein level, these findings were in accordance with the observation that protein in general and albumin level in particular remains unchanged in acute liver damage (Anand et al, 1994). This brief period might not be sufficient to demonstrate any rise in serum protein levels.…”
Section: Discussionsupporting
confidence: 87%
“…Dwivedi et al (1994), Srivastava et al (1992) and Khan and Gilani (in press) reported that Terminalia bellerica lowers the arterial blood pressure. A water soluble fraction obtained from the defatted fruits of Terminalia bellerica caused protection against CCl 4 -induced liver injury in rodents (Anand et al, 1994). In a clinical study, Terminalia bellerica was found to possess antispasmodic, antiasthmatic and antitussive effects (Trivedi et al, 1979).…”
Section: Introductionmentioning
confidence: 97%
“…The phenolic moiety of emodin might interact with membrane components to break the peroxidative chain reaction to stabilize the membrane. Various plant extracts and their active principles, that is Terminalia belerica 43 and gallic acid 40 have also been reported to possess membrane stabilizing effects against oxidative insult. The BSP is metabolized by MDMEs in liver and increase in BSP retention in plasma clearly indicates the fall in excretory capacity of liver 44 or unavailability of MDMEs in toxic conditions 45 .…”
Section: Discussionmentioning
confidence: 99%